2022
DOI: 10.1371/journal.ppat.1009717
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum membrane protein complex localizes to the mitochondrial - endoplasmic reticulum interface and its subunits modulate phospholipid biosynthesis in Trypanosoma brucei

Abstract: The endoplasmic reticulum membrane complex (EMC) is a versatile complex that plays a key role in membrane protein biogenesis in the ER. Deletion of the complex has wide-ranging consequences including ER stress, disturbance in lipid transport and organelle tethering, among others. Here we report the function and organization of the evolutionarily conserved EMC (TbEMC) in the highly diverged eukaryote, Trypanosoma brucei. Using (co-) immunoprecipitation experiments in combination with mass spectrometry and whole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…(Volkmar and Christianson, 2020). In a study by Iyer et al (2022), biochemical, proteomic, and imaging approaches were used to study the EMC (TbEMC) in T. brucei. This study revealed that TbEMC is formed by 9 subunits with 20-40% of similarity with yeast and human homologs.…”
Section: The Second-order Role Of Er In Trypanosomatidsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Volkmar and Christianson, 2020). In a study by Iyer et al (2022), biochemical, proteomic, and imaging approaches were used to study the EMC (TbEMC) in T. brucei. This study revealed that TbEMC is formed by 9 subunits with 20-40% of similarity with yeast and human homologs.…”
Section: The Second-order Role Of Er In Trypanosomatidsmentioning
confidence: 99%
“…( Volkmar and Christianson, 2020 ). In a study by Iyer et al. (2022) , biochemical, proteomic, and imaging approaches were used to study the EMC (TbEMC) in T. brucei .…”
Section: The Second-order Role Of Er In Trypanosomatidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss or reduction of EMC members results in defective cellular processes and renders them susceptible to various viruses 16–19 . Moreover, elimination or reduced levels of a single EMC subunit leads to growth defects in Trypanosoma brucei procyclic forms due to disruption of ab initio synthesis of phosphatidylcholine (PC) and phosphatidylethanolamine (PE) 20 …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Moreover, elimination or reduced levels of a single EMC subunit leads to growth defects in Trypanosoma brucei procyclic forms due to disruption of ab initio synthesis of phosphatidylcholine (PC) and phosphatidylethanolamine (PE). 20 Recent studies underscore the vital role of EMC in maintaining ER function, impacting processes such as protein and lipid synthesis, organelle communications, ER stress, viral infection, and various diseases. 7,8,[21][22][23][24][25][26] Given the newfound significance of EMC in biochemical processes and diseases, investigations into their structure, functions, and pathogenesis-related studies have become an area of considerable interest.…”
mentioning
confidence: 99%